THE INFLUENCE OF STRATEGIC SERVICE COMPETENCE CHAIN MANAGEMENT TO RELATIONSHIP MARKETING BASED PERFORMANCE - Rudyanto Rudyanto (Business and Entrepreneurial Review, 2010)
Using the relational marketing perspective theory of the firm to establish a theoritical foundation, this study serves to fill a gap in the supply chain service management literature with respect tosupply chain service management performance and sales performance antecedent such as strategic service competence, degree of suppliers’ integration, the perceived status function of supply chain service management, and firm size as a moderated variable.The sample used for this study consist of 216 respondents from 23 different manufacturers which had a network of suppliers, and about 73.1% had corporate-wide decision-making responsibilities. Confirmatory factor analyses provided evidence of adequate model fit, convergent and discriminant validity for the underlying variables, and respective factors in the model. The conceptual model and the hypothesized are tested using Structural Equation Modeling. Support was found for the causal relationship between variables in the models that strategic service competence based on relationship marketing, degreesupplier’s integration and perceived status function of supply chain service management by simultan directly had positive contribution on supply chain service management performance;interestingly, strategic service competence through degree supplier’s integration, perceived status function of supply chain service management and supply chain service management performance had indirectly positive contribution on sales performance, and firm size as moderated had no contribution on relation between strategic service competence based on relationship marketing and supply chain service management’s performance. This research indicated that the degree suppliers’ integration and its perceived status function of supply chain service management are necessary resources to strengthen strategic competitive advantage of the firms. Professionals inthe supply chain service management are endeavoring to improve relationship suppliers and to integrate these service activities in the strategy will increase firm’s performance